2019
DOI: 10.1111/ivb.12256
|View full text |Cite
|
Sign up to set email alerts
|

Benthic ctenophore (Order Platyctenida) reproduction, recruitment, and seasonality in south Florida

Abstract: Reproductive structures, modes, and seasonal patterns of size-class abundances are examined in two benthic platyctene (Family Coeloplanidae) ctenophore species present in dissimilar shallow marine environments in subtropical southeast Florida.Coeloplana waltoni, a minute (1-3 mm body length) epizoic associate of octocorals, occurs in exposed environments often under turbulent conditions, and Vallicula multiformis (2-10 mm) commonly occurs epiphytically on macroalgae in protected, calmwater environments. Reprod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Despite the different and continuous faunal monitoring (mainly benthic studies) performed by the project BDMY-UNAM in the Mexican Caribbean and the southern Gulf of Mexico, only two individuals of V. multiformis have been observed. The reproductive strategy of this species (Rankin, 1956; Glynn et al ., 2019) allows it to have high abundances during different seasons in some regions of its spatial distribution (e.g. Rankin, 1956; Eldredge and Miller, 1995; Glynn et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the different and continuous faunal monitoring (mainly benthic studies) performed by the project BDMY-UNAM in the Mexican Caribbean and the southern Gulf of Mexico, only two individuals of V. multiformis have been observed. The reproductive strategy of this species (Rankin, 1956; Glynn et al ., 2019) allows it to have high abundances during different seasons in some regions of its spatial distribution (e.g. Rankin, 1956; Eldredge and Miller, 1995; Glynn et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In just 20 years, individuals of O. mirabilis have colonized coastlines spanning more than 6000 km of latitude (Tavares et al 2021), from their first reported presence in southern Brazil (Hendler et al 2012) northward along the South American coast to the Caribbean Sea (Hendler and Brugneaux 2013;Ferry et al 2020) and southeastern Florida (Glynn et al 2019). Their northern-most occurrence on the Florida east coast, observed on 28 September 2019, was at Deerfield Beach, 26.3184°N, 80.0998°W (Glynn et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Ophiothela has a widespread distribution that is continuing to expand. Recently, Ophiothela mirabilis was observed associated with octocorals at Dania Beach, Florida, USA (Glynn et al ., 2019). To date, Ophiothela has not been reported from the northern- and southern-most regions of the Pacific coast of the Americas.…”
Section: Discussionmentioning
confidence: 99%